If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -4 = 2b + 10 Reorder the terms: -4 + 3b = 2b + 10 Reorder the terms: -4 + 3b = 10 + 2b Solving -4 + 3b = 10 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. -4 + 3b + -2b = 10 + 2b + -2b Combine like terms: 3b + -2b = 1b -4 + 1b = 10 + 2b + -2b Combine like terms: 2b + -2b = 0 -4 + 1b = 10 + 0 -4 + 1b = 10 Add '4' to each side of the equation. -4 + 4 + 1b = 10 + 4 Combine like terms: -4 + 4 = 0 0 + 1b = 10 + 4 1b = 10 + 4 Combine like terms: 10 + 4 = 14 1b = 14 Divide each side by '1'. b = 14 Simplifying b = 14
| 2(4-1,9z)=0,8-0,2z | | 2(4x+10)=2x+-4 | | .26=ln(x) | | 6(x+4)=3(4x+2) | | 28y+3=47 | | 11y+6x=17 | | 40x+16(1.5x)=630.00 | | 6-(2w+1)=5w-2(5+w) | | -15X+5=-9x-21 | | 6(2m-5)-2(5-2m)=15+6(m+1) | | log(4x+5)=2 | | -6+2-3a=-7+a-11 | | C=d-1 | | 20-(x+5)=6x-6 | | 4d(d+2)-2d=3(2+d) | | 3+5x=9+3x | | 1/2(2x-4)=3x+5/6 | | [3v-2]/5=4 | | 9y-5-6y+1=0 | | 35-7x=9(3x+3) | | (4x^2+3)(x-4)(x+4)=0 | | 8y+13=5y-5 | | (y+.33)(y-.33)= | | [1-6n]+3=46 | | 5x^2-6x+5= | | 0.1(x+250)=5,000 | | 8x^5+26x^3-24x=0 | | x=1056-.1x | | 7(z-5)+1=2-3(2z-1) | | 2x+6x-14=22 | | [4x+4]=28 | | 12+x=-3x(4-x) |